ECONOMIC IMPACT ASSESSMENT OF VILLAGE FUND IN INDONESIA USING INTER-REGIONAL INPUT OUTPUT ANALYSIS - ILHAM TOHARI (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2022)
The economic development of a region/country is marked by development in various sectors and regions through private or public spending. In 2017, village fund (as one of government expenditure) has induced and supported sectors such as public administration, human health and social works, education, manufacturing industries and other service activities in any region. This study aims to analyze the impact of the 2017 village fund program realization on the Indonesian economy, such as the impact on final demand, household income, and employment coverage. The method used in this research is Inter-Regional Input Output (IRIO) analysis using the IRIO Indonesia Table in 2016 domestic transactions on producer prices classification 102 x 102 sectors (6 regions and 17 sectors). The results of this study show Indonesia's total domestic output in 2017 for the realization of the village fund budget of IDR 98 trillion. Meanwhile, Village Fund 2017 program stimulated a total salary increase of IDR 26.980 trillion or 648,132 additional workers or contributed to employment increase during 2017 as 13.12%. The results of the analysis of the output multiplier and the income multiplier show that, if we viewed in sectoral details, the electricity and gas sector and the manufacturing industry sector have more roles in increasing output compared to other sectors.